Analysis and simulation of desalination processes via advanced low-dimensional material systems - Ang, Elisa Yun Mei (Nanyang Technological University, 2020)
Desalination is seen as a possible sustainable solution for global water crisis due to the large amount of salt-water available on Earth. However, for desalination to be used for the large-scale production of potable water, its cost must reduce. Low-dimensional material membranes have the potential to significantly reduce desalination cost. This is due to their ultra-low thickness, which results in orders of magnitude increase in permeability when compared to conventional polymeric desalination membrane. This significant increase in permeability can lead to a huge reduction in desalination cost, operating close to the thermodynamic minimum energy required for desalination. Due to the difficulty in fabrication and manipulation of low-dimensional material systems currently, computational simulation is the method of choice to further advance this field at this point in time. This project deploys molecular dynamics (MD) simulation to explore design ideas for low-dimensional material membrane systems and investigate the feasibility of using such systems to overcome the high cost of desalination. Two low-dimensional material membrane designs are proposed and tested extensively, namely the graphene slit membrane, and the transverse flow carbon nanotube membrane (TFCM). The TFCM is found to have the best desalination performance and its design parameters were optimized. The current project also performed comparison studies against experimental data on the anti-fouling properties of graphene films with overlapping grain boundaries. Different two-dimensional materials other than carbon were also considered, including borophene, MXene and molybdenum disulfide. Finally, the thesis report ends off with some recommended future directions that can be taken to further advance the field of low-dimensional material membrane.